2010
DOI: 10.1227/01.neu.0000367551.41503.58
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Decompression of the Ulnar Nerve at the Elbow

Abstract: The endoscopic technique for ulnar nerve entrapment syndrome seems to be safe and effective. However, particularly in patients with a thick subcutaneous fat layer, identification of the nerve at the sulcus is difficult and possible more risky than in open simple decompression. A randomized prospective study should be performed to further evaluate the value of this new technique in the treatment of ulnar nerve entrapment syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 19 publications
(17 reference statements)
0
9
0
7
Order By: Relevance
“…In a study recently published [9], the authors found improvement after steroid injection in patients with an UNE; however, the study group is somewhat different with our group because they included patients who were sent for surgery but refused surgical treatment. In general when ulnar nerve compression by the arcuate ligament is the case, often associated with severe loss of motor function, surgical treatment is the primary choice [10,11]. When these patients are treated with corticosteroid injection, a follow‐up period of 3 months is too long and these patients should be admitted to surgery in time.…”
Section: Discussionmentioning
confidence: 99%
“…In a study recently published [9], the authors found improvement after steroid injection in patients with an UNE; however, the study group is somewhat different with our group because they included patients who were sent for surgery but refused surgical treatment. In general when ulnar nerve compression by the arcuate ligament is the case, often associated with severe loss of motor function, surgical treatment is the primary choice [10,11]. When these patients are treated with corticosteroid injection, a follow‐up period of 3 months is too long and these patients should be admitted to surgery in time.…”
Section: Discussionmentioning
confidence: 99%
“…Desde que fue descrita por primera vez por Tsai y colegas 13 han aparecido múltiples trabajos que han dado buenos resultados con la liberación endoscópica del túnel cubital y diversas modificaciones de la técnica original. 11,12,13,14,15 En estudios que comparan la liberación endoscópica vs abierta, la descompresión endoscópica mostró menor índice de complicaciones y mejores resultados a corto plazo en términos de reincorporación laboral precoz, satisfacción del paciente y alivio del dolor. 2,3,4,5,6,7,8,9,10,11,12,13,14,15,16 Con la liberación endoscópica del nervio cubital se pretende ofrecer varios beneficios al paciente en relación a la cirugía abierta, como minimizar el riesgo de lesión de estructuras adyacentes, reducir morbilidad del área quirúrgica, una recuperación más rápida y resultados estéticos más satisfactorios por el tamaño de la incisión.…”
Section: Discussionunclassified
“…11,12,13,14,15 En estudios que comparan la liberación endoscópica vs abierta, la descompresión endoscópica mostró menor índice de complicaciones y mejores resultados a corto plazo en términos de reincorporación laboral precoz, satisfacción del paciente y alivio del dolor. 2,3,4,5,6,7,8,9,10,11,12,13,14,15,16 Con la liberación endoscópica del nervio cubital se pretende ofrecer varios beneficios al paciente en relación a la cirugía abierta, como minimizar el riesgo de lesión de estructuras adyacentes, reducir morbilidad del área quirúrgica, una recuperación más rápida y resultados estéticos más satisfactorios por el tamaño de la incisión. 5,6,7,8,9,10,11,12,13,14,15,16,17 Además de lo anterior, las técnicas endoscópicas han demostrado ser seguras y eficaces, 5,6,7,8,9,10,11,12,13,14,15,16,17,…”
Section: Discussionunclassified
See 2 more Smart Citations